Danaides como Suplicantes y Refugiadas: Le Supplici en Siracusa - Molina Zorrilla, Isidro; Carrillo Rodríguez, Míriam; Balaskas, Vasileos (Universidade de Aveiro, 2020)
In this article, we analyze Moni Ovadia’s Le Supplici, an adaptation of Aeschylus’s The Suppliants performed in 2015 in Syracuse. It situates this work within its literary, sociopolitical and genre contexts. Themes such as forced migration and funda‐ mental human rights connect the work to the present migratory crisis and to the situation of refugees, understood as a social movement that gives rise to new interpretations of the European national space.
Keywords: Emigración e inmigración - En la literatura; Derechos humanos - En la literatura; Esquilo - Crítica e interpretación; Aeschylus; The Suppliants; Ovadia; Ethnoscapes; Las suplicantes